An analysis of company choice preference to carbon tax policy in China. (15th September 2015) - Liu, Xianbing; Wang, Can; Niu, Dongjie; Suk, Sunhee; Bao, Cunkuan
Abstract: This paper summarizes an analysis of choice preferences of Chinese companies to the design options of carbon tax policy. The data were collected from 201 companies, with around half of them based in the western Shanxi Province and the other half from the eastern Jiangsu Province. Modeling analysis of the discrete choice dataset confirms the statistically significant relationships between the company's preferences to carbon tax policy with the policy attributes, including tax rate, tax relief measures and the revenue utilization. From the viewpoint of Chinese businesses, the option of carbon tax policy with tax rate at 10–30 Yuan/t-CO2, allowing tax relief to energy-intensive sectors, using the revenues specific for climate change and starting as early as the 13th five-year plan period (2016–2020) would be preferable and realistic. The results of this research may be referred for the discussions and development of carbon tax policy in China. Highlights: This paper analyzes company's choice preference to carbon tax policy in China. The dataset was collected from 201 companies by a choice experiment survey. The policy attributes significantly associated with the choices were identified. The results reveal the preferable option of carbon tax for the businesses of China.